2012
DOI: 10.1007/s00436-012-2936-4
|View full text |Cite
|
Sign up to set email alerts
|

Alaria alata in wild boars (Sus scrofa, Linnaeus, 1758) in the eastern parts of Germany

Abstract: Over the last decade, incidental findings of Alaria alata in stocks of German wild boar during the official Trichinella inspection have been increased. As early as 2006, the German Federal Institute for Risk Assessment pointed out the possible health risk to the consumer posed by this trematode. However, at that time, reliable data concerning the prevalence of the parasite in German wild boars and feral pigs were lacking especially because no appropriate detection method was available. The development of the A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
25
2

Year Published

2013
2013
2018
2018

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 34 publications
(30 citation statements)
references
References 5 publications
3
25
2
Order By: Relevance
“…Mesocercariae prevalence studies in wild boar muscle samples from East Germany showed that false results occurred in 11.5% of the samples when TIM was used (Riehn et al 2012). In the present study, using standard protocol of TIM together with additional mesocercariae counting in the sieve, we established mesocercariae occurred significantly more frequently than found only in the Petri dish, indicating that routinely we obtain 58.4% of false results originally.…”
Section: Discussionsupporting
confidence: 51%
See 1 more Smart Citation
“…Mesocercariae prevalence studies in wild boar muscle samples from East Germany showed that false results occurred in 11.5% of the samples when TIM was used (Riehn et al 2012). In the present study, using standard protocol of TIM together with additional mesocercariae counting in the sieve, we established mesocercariae occurred significantly more frequently than found only in the Petri dish, indicating that routinely we obtain 58.4% of false results originally.…”
Section: Discussionsupporting
confidence: 51%
“…However, studies which used AMT have greater reliability. Studies in Germany using AMT showed A. alata prevalence 11.5% in wild boars and 33.3% in raccoons (Riehn et al 2012;Rentería-Solís et al 2013), while during similar study in Austria prevalence in wild boars was 6% (Paulsen et al 2014).…”
Section: Introductionmentioning
confidence: 88%
“…However, this does not bias the risk factors analysis (in particular, the choice of pooling samples were not dependant on hunting area, season or on the age class). A recent study reports an estimated percentage of 11.5% of false negative results for the detection of A. alata using the Trichinella inspection methods instead of the Alaria migration technique, under field conditions (Riehn et al, 2012). Using this estimate to correct the prevalence rates obtained in the four hunting areas where the circulation of A. alata mesocercaria can be considered enzootic (hunting areas denoted A, B, C and D above) results in prevalence rates 16%, 20%, 26.7% and 30.7%.…”
Section: Discussionmentioning
confidence: 97%
“…A new detection method was designed (Riehn et al, 2010(Riehn et al, , 2011 and resistance to freezing has been tested (Portier et al, 2011). Though wild boars are not an obligatory host to A. alata mesocercaria and their suspected sources of infection (amphibians) are not the heart of their diet, high prevalence and heavy parasite burdens have been observed in different European landscapes (Mileševic et al, 2004;Möhl et al, 2009;Riehn et al, 2012). Infection by A. alata mesocercaria does not seem to have an impact on the health of wild boars, but the presence of A. alata mesocercaria in this species represents a potential risk for human because of new cooking methods (barbecuing increasingly used for game meat), suspected cases of alariosis due to A. alata (Prokopowicz et al, 2005) and confirmed cases of alariosis due to mesocercaria of American Alaria species in the USA and Canada Freeman et al, 1976;McDonald et al, 1994).…”
Section: Introductionmentioning
confidence: 99%
“…A tenfold higher T. vulpis detection rate (38.5%) was found in wild wolves in Poland ( 21 ), and A. alata rates ranged from 17.3% in Byelorussia, known today as Belarus ( 31 ), up to 80.1% in Poland ( 10 ). In recent years, A. alata mesocercariae have increasingly been detected in meat of wild boar in Germany ( 32 ), indicating that feeding of wild boar to wolves serves as a source of infection. As mentioned above, almost all zoos fed game to wolves.…”
Section: Discussionmentioning
confidence: 99%